EDUCATIONAL MANAGEMENT IN THE LIGHT OF ISLAMIC STANDARDS - Muhammad Sodiqul Fikri; Rezki Oktoberi; Yuniar; Idham Kholid (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article provides a comprehensive examination of educational management in the light of Islamic standards by exploring its theological, philosophical, and practical foundations derived from the Qur’an, the Hadith, and both classical and contemporary Muslim scholarship. Islamic standards emphasize that education is not solely the transmission of knowledge but also the cultivation of moral character, ethical behavior, and spiritual consciousness. Core principles such as tawhid (oneness of God), shura (consultation), amanah (trust and accountability), ‘adl (justice), and ihsan (excellence) serve as essential foundations for planning, organizing, leading, and evaluating educational institutions. This article further elaborates on prophetic leadership as an ideal model for educational administrators, the Tawhidic curriculum that integrates religious and worldly sciences, and teacher professionalism framed through the roles of mu’allim (knowledge transmitter), murabbi (character nurturer), and muaddib (ethics cultivator). The study also examines Islamic financial management through zakat, waqf, and voluntary charity as sustainable instruments for educational development.